ANALYSIS OF SUPPORTING FACILITIES FOR PASSENGERS WITH DISABILITIES AND THE ELDERLY TO IMPROVE SERVICES AT THE AJI PANGERAN TUMENGGUNG PRANOTO AIRPORT SAMARINDA - Darma Putra Ananda K., Tjokorda; Hariyanto, Didi; Musadek, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Aji Pangeran Tumenggung Pranoto Samarinda Airport, located in Samarinda, East Kalimantan, provides facilities such as wheelchairs, guiding blocks, special toilets, priority seats, elevators, and staff assistance for passengers with disabilities and the elderly. Services include guidance from terminal arrival, check-in, to boarding, aiming to meet passenger needs and ensure travel comfort. This study aims to identify challenges and strategies to improve such services.Using qualitative methods, data were collected through observation, interviews, documentation, and literature review. The focus was on facilities for passengers with disabilities and the elderly, involving the head of service and cooperation, the information management coordinator, and information officers.Findings revealed several issues: damaged guiding blocks, inactive arrival lifts, ramps not meeting slope standards, lack of designated parking, limited wheelchairs, and staff lacking sign language skills. Strategies include improving and maintaining facilities, training staff in sign language, and conducting regular monitoring and evaluation to ensure service quality.